2020
DOI: 10.1017/s1463423620000018
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an instrument for measuring competencies on public health informatics of primary health care worker (PHIC4PHC) in Indonesia

Abstract: Abstract Because of the increasing adoption and use of technology in primary health care (PHC), public health informatics competencies (PHIC) are becoming essential for public health workers. Unfortunately, no studies have measured PHIC in resource-limited setting. This paper describes the process of developing and validating Public Health Informatics Competencies for Primary Health Care (PHIC4PHC), an instrument for measuring PHC workers’ competencies in public health infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Some nurses were unsure of their ability to create multimedia files, use statistical software to analyse study data, troubleshoot typical computer errors, and assemble a computer. This supports the findings of a Delphi survey in which nurses from Indonesia reported that these skills were irrelevant to their daily work activities (Rachmani et al, 2020). The study identified no significant association between age and skills in EHR use and between years of work experience and EHR use.…”
Section: Discussionsupporting
confidence: 82%
“…Some nurses were unsure of their ability to create multimedia files, use statistical software to analyse study data, troubleshoot typical computer errors, and assemble a computer. This supports the findings of a Delphi survey in which nurses from Indonesia reported that these skills were irrelevant to their daily work activities (Rachmani et al, 2020). The study identified no significant association between age and skills in EHR use and between years of work experience and EHR use.…”
Section: Discussionsupporting
confidence: 82%
“…The definitions used are either the results of scoping reviews or frameworks where many individual results have been merged (15/46, 33%) [4,10,23,26,28,33,37,42,44,46,48,51,52,59,61]. Alternatively, they are based on other, explicitly named works, such as DigComp 2.2 [7] (4/46, 9%) [22,29,54,56]; the European framework for the digital competence of educators [63] (1/46, 2%) [27]; the technology acceptance model [64] and the unified theory of acceptance and use of technology [65] (1/46, 2%) [11]; the accreditation of competence in information and communication technologies by the government of Catalonia [66] (1/46, 2%) [53]; the Educause Center for Analysis and Research [67] (1/46, 2%) [60]; the General Confidence with Computer Use Scale [68] (1/46, 2%) [32]; the eHealth literacy questionnaire [69] (1/46, 2%) [40]; the eHealth literacy assessment toolkit [70] (1/46, 2%) [34]; the Self-Assessment of Nursing Informatics Competencies Scale [71] (1/46, 2%) [24]; a scale assessing the informatics competencies for nurses [72] (1/46, 2%) [39]; a scale assessing digital literacy with regard to information and communication technology [73] (1/46, 2%)…”
Section: Most Of the Papers Provided Definitions In Which Digital Com...mentioning
confidence: 99%
“…Multiple subcompetences of technical competences were identified: the ones mentioned most often were basic computer competence, meaning knowledge of different computer components and basic computer concepts [21,32,43]; and skills in using hardware (eg, switching equipment on and off and operating input and output devices) [49,62]. Internet use, consisting of navigating the internet, knowledge of various internet sources, and finding and downloading articles, is part of basic computer competence [24,25,28,37,43,52,62]. The users should be able to use and install software [24,28,32,33,37,49,52,62] and especially be able to use information and communication technology, including understanding the basic concepts and components of information and communication technology and designing, creating, integrating, publishing, and revising content [4,9,22,23,27,[35][36][37][38]41,[43][44][45][47][48][49]53,54,56,57,62].…”
Section: Technical Competencesmentioning
confidence: 99%
See 2 more Smart Citations